Ophiopogonin D of Ophiopogon japonicus ameliorates renal function by suppressing oxidative stress and inflammatory response in streptozotocin-induced diabetic nephropathy rats - Qiao,Yanhong (2020)
Ophiopogonin D (OP-D) is the principal pharmacologically active ingredient from Ophiopogon japonicas, which has been demonstrated to have numerous pharmacological activities. However, its protective effect against renal damage in streptozotocin (STZ)-induced diabetic nephropathy (DN) rats remains unclear. The present study was performed to investigate the protective effect of OP-D in the STZ-induced DN rat model. DN rats showed renal dysfunction, as evidenced by decreased serum albumin and creatinine clearance, along with increases in serum creatinine, blood urea nitrogen, TGF-β1, and kidney hypertrophy, and these were reversed by OP-D. In addition, STZ induced oxidative damage and inflammatory response in diabetic kidney tissue. These abnormalities were reversed by OP-D treatment. The findings obtained in the present study indicated that OP-D might possess the potential to be a therapeutic agent against DN via inhibiting renal inflammation and oxidative stress.